How robotics is changing the world - Hulick, Kathryn (How science changed the world., 2019)
Examines how the invention of robots has changed daily life in positive and negative ways. Discusses their origins, evolution, and possible future. Includes a timeline, color photographs, sidebars, a glossary, and further resources.